The use of a patient-based questionnaire (the Oxford Shoulder Score) to assess outcome after rotator cuff repair. - Olley, L; Carr, A (2008)
INTRODUCTION: It is increasingly important for surgeons to monitor the outcome of their practice for the purpose of audit. The main difficulty has been the lack of appropriate methods of assessing outcome. Outcome has traditionally been assessed by clinical means which can be inaccurate, irreproducible and subject to surgeon bias. In addition, the perspective of the patient and surgeon may differ with respect to outcome and interest has grown in patient-based scoring systems. The Oxford Shoulder Score (OSS) is one such patient-based scoring system. The main aim of this study was to assess whether a patient-based questionnaire, in this case the OSS, could be effectively used to audit outcome from shoulder surgery. A secondary aim was to assess the value of gathering outcome information by post. PATIENTS AND METHODS: A total of 24 patients (14 male; median age 59 years; age range, 43-73 years) who had completed a pre-operative OSS questionnaire and had undergone rotator cuff repair were included in the study. Participants were assessed postoperatively at regular intervals using the OSS at hospital visits and by postal questionnaire. RESULTS: The completion level for the OSS was 97% and the response rate to the postal questionnaire was 96%. At 3 months' post-surgery, 21 of 24 patients had improved; at final review (16-37 months), 23 patients had improved following surgery. The OSS was observed to be a robust tool for the quantitative assessment and tracking of patient outcomes after surgery. CONCLUSIONS: This study shows the value of using a postal questionnaire to follow-up patients after surgery and demonstrates the successful use of a patient-based questionnaire to audit the outcome from shoulder surgery.